2019
DOI: 10.1002/tcr.201900014
|View full text |Cite
|
Sign up to set email alerts
|

Metal Nanoparticles Syntheses on Ionic Liquids Functionalized Mesoporous Silica SBA‐15

Abstract: Supported metal nanoparticles hold great promise in heterogeneous catalysis as active and reusable catalysts for various organic transformations. Preparation methods of metal nanoparticles with excellent control over size, shape, and morphology on supports has significantly advanced to improve the performances of the resulting catalysts. Here, we aim to discuss the development of supported metal nanoparticles on mesoporous silica SBA‐15 in the presence of immobilized ionic liquids mostly based on examples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 94 publications
(169 reference statements)
0
10
0
Order By: Relevance
“…Besides small organic molecules, ionic liquid (IL) was also grafted on silicas for the stabilization of metal NPs. [56][57][58][59][60] Leitner et al demonstrated the versatility of this molecular approach for the preparation of multifunctional catalysts. 56 Moreover, polymers could also be incorporated in the nanopore of mesoporous silicas by dispersing the polymers on the mesoporous silicas or by in situ polymerization in mesoporous silicas.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…Besides small organic molecules, ionic liquid (IL) was also grafted on silicas for the stabilization of metal NPs. [56][57][58][59][60] Leitner et al demonstrated the versatility of this molecular approach for the preparation of multifunctional catalysts. 56 Moreover, polymers could also be incorporated in the nanopore of mesoporous silicas by dispersing the polymers on the mesoporous silicas or by in situ polymerization in mesoporous silicas.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…By varying the nature and the quantity of the ionic liquids, the size and shape of these nanoparticles in the mesoporous channels of SBA‐15 can be controlled. For example, AuPd nanoparticles have been synthesized over SBA‐15 functionalized with imidazolium groups which showed excellent activity toward the hydrogenation of 4‐nitrophenol . These results reveal that non‐ionic surfactants can be effectively used for the introduction of varieties of functional groups in the mesoporous inorganic oxides to develop a series of porous organic‐inorganic hybrid materials with different properties and also for different applications.…”
Section: Synthesis Of Organo‐functionalized Molecular Sievesmentioning
confidence: 99%
“…The SILCs were initially developed using inorganic supports like SBA-15 [ 9 ] and heteropolyacids [ 10 ].…”
Section: Introductionmentioning
confidence: 99%